Working for Patients: NHS reform and drug budgets. Issue 17 (5th September 2014) - Baines, Darrin
<x xml:space="preserve">Abstract</x> In our series on the history of prescribing policy, Dr Darrin Baines traces how successive governments have attempted to curb drug costs. Here, he describes the controversial reforms introduced following the publication of Working for Patients in 1989.